Surveillance of omadacycline activity tested against clinical isolates from the United States and Europe: Results from the SENTRY Antimicrobial Surveillance Programme, 2017. (December 2019) - Huband, Michael D.; Pfaller, Michael A.; Shortridge, Dee; Flamm, Robert K.
Highlights: 98.7% of Staphylococcus aureus isolates (n = 2684) were susceptible to omadacycline. 98.6% of Streptococcus pneumoniae isolates (n = 968) were susceptible to omadacycline. All Streptococcus anginosus isolates (n = 50) were susceptible to omadacycline. 87.5% of Klebsiella pneumoniae isolates (n = 1269) were susceptible to omadacycline. Omadacycline recently received United States Food and Drug Administration approva Abstract: Objectives: Omadacycline is an aminomethylcycline antibacterial (oral and intravenous once-daily formulation) that recently (October 2018) received United States Food and Drug Administration (FDA) approval for the treatment of acute bacterial skin and skin structure infections (ABSSSIs) and community-acquired bacterial pneumonia (CABP) against selected organism groups. This study tested omadacycline and comparators against 14 000 non-duplicate bacterial isolates that were prospectively collected during 2017 from medical centres in Europe (EUR; 7000 isolates) and the United States (USA; 7000 isolates). Methods: Omadacycline was tested by broth microdilution following Clinical and Laboratory Standards Institute M07-A11 (2018) methods. Results: A total of 98.7% of Staphylococcus aureus isolates were susceptible to omadacycline (MIC50/90, 0.12/0.25 mg/L; ABSSSI breakpoints) including 96.5% of methicillin-resistant Staphylococcus aureus (MRSA), 99.8% of methicillin-susceptible Staphylococcus aureus, and 93.9% of tetracycline-resistant strains. Omadacycline activity was similar for Streptococcus pneumoniae (MIC50/90 0.06/0.12 mg/L; 98.6% susceptible [CABP breakpoints]), Streptococcus anginosus group (MIC50/90 0.06/0.06 mg/L; 100.0% susceptible [ABSSSI breakpoints]), and Streptococcus pyogenes (MIC50/90 0.06/0.12 mg/L; 97.7% susceptible [ABSSSI breakpoints]). Omadacycline demonstrated activity against Enterobacter cloacae species complex isolates (MIC50/90, 2/4 mg/L; 91.2% susceptible [ABSSSI breakpoints]), Klebsiella pneumoniae (MIC50/90, 2/8 mg/L; 87.5% susceptible [CABP and ABSSSI breakpoints]), and inhibited 99.1% of Escherichia coli (MIC50/90, 0.5/2 mg/L) isolates at ≤ 4 mg/L. Omadacycline was active against Haemophilus influenzae (MIC50/90, 0.5/1 mg/L; 99.8% susceptible [CABP breakpoints]), including all β-lactamase positive isolates, and inhibited 100.0% of Moraxella catarrhalis isolates at ≤ 0.25 mg/L. Conclusions: The potent activity of omadacycline against Gram-positive and Gram-negative bacteria indicates that omadacycline merits further study in serious infections in which multidrug resistance and mixed Gram-positive and Gram-negative infections may be of concern.